PENGARUH LATIHAN MOBILISASI MIRING KANAN MIRING KIRI TERHADAP LAMA HARI RAWAT PADA PASIEN PASCA APENDEKTOMI DI RSD MANGUSADA - Ni Kadek Ratna Kurniari; N. M. A Sukmandari; Si Putu Agung Ayu Pertiwi Dewi (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Background: The length days of treatment for appendectomy is due to the presence of wounds that require healing The length days of hospitalization can be overcome by providing Left Turn/ Right Tilt oblique as early as possible in post appendectomy surgery patients. Objective: This study purpose to determine the effect of Left Turn/ Right Tilt mobilization exercises on the length of hospitalization in post appendectomy patients at RSD Mangusada. Method: The research was conducted with a Post-test design Only With Control Group Design. The number of samples were 21 people from each group using purposive sampling technique. Data were collected using observation sheets for length day of stay. Data were analyzed using the Mann Whitney. test. Results: The results of the study in the experimental group with an average length of stay of 2.61 days, while in the correlation between the effect of left turn/ right tilt mobilization exercise on the length day of stay in post appendectomy patients obtained p value <0.001. Conclusion: The effect of left turn/ right tilt mobilization exercise on length of hospitalization in post- appendectomy patients at RSD Mangusada. The recommendations of this study are expected to be input for nurses to always provide right and left oblique as early as possible in postoperative patients.